Addressing Health Disparities: The Health Department Nurse Lead Executive's Relationship to Improved Community Health. Issue 2 (March 2022) - Kett, Paula M.; Bekemeier, Betty; Herting, Jerald R.; Altman, Molly R.
Abstract : Context: The nurse-trained local health department (LHD) lead executive has been shown to be positively associated with LHD performance; however, no other research has explored whether this association translates to improved community health. Objective: To investigate the relationship between the type of LHD leadership—whether or not the lead executive is a nurse—and changes in health outcomes. Design: This study used a multivariate panel time series design. Each model was estimated as a pooled time series and using time and unit fixed effects, with a 1-year lag used for all covariates and the main predictor. Setting: A national, county-level data set was compiled containing variables pertaining to the LHD, community demographics, and health outcomes for the years 2010-2018. Participants: The unit of analysis was the LHD. The data set was restricted to those counties with measurable mortality rates during at least 8 of the 9 time periods of the study, resulting in a total of 626 LHDs. Main Outcome Measures: The outcomes of interest were changes in 15- to 44-year-old all-cause mortality, infant mortality, and entry into prenatal care. Results: In models with combined time and unit fixed effects, a significant relationship exists between a nurse-led LHD and reduced mortality in the 15- to 44-year-old Black population (−5.2%, P < .05) and a reduction in the Black-White mortality ratio (−6%, P < .05). In addition, there is a relationship between the nurse-led LHD and a reduction in the percentage of the population with late or no entry to prenatal care. Conclusions: The evidence presented here helps connect the known positive association between nurse lead executives and LHD performance to improvements in community health. It suggests that nurse leaders are associated with health improvements in line with addressing health inequities. Abstract : Supplemental Digital Content is Available in the Text.